Artificial Intelligence tools and its role in creating a good E-learning environment - Raed Ashraf Kamil Albadri, Bilal A. Tuama (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The descriptive method was used in this study, by creating a questionnaire form using Google Forms, submitted by the faculty and students' communication sites, to answer them online, Results showed that 85% of students in the pure and applied scientific departments prefer online lectures and tests, while 35% of the students in humanitarian sections preferred is not relying on it, and 65% of them preferred to use technology with education. The study recommends that the adoption of modern technologies in educational systems it increases the comprehension of information during the lectures, through the presented ways, and following methods that make the student understanding and memorizing more easier , and the e-learning provides a virtual environment that increases the possibility of communicat the students with each other , also between students and professors, it allows the student to access educational materials at any time and anywhere, and helps the teacher to reach his students, inform them of important matters, and send educational materials to them.